DAMPAK ROLE PLAY METHOD TERHADAP PEMBELAJARAN KETERAMPILAN BERBICARA SISWA KELAS XI SMAN 1 MONTONG GADING - Masud, Lalu; Irfan, Moh; Ernawati, Titin; Muttaqin, Zainul (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2022)
The purpose of this study was to determine the impact of the application of the Role Play Method on speaking skills in class XI students of SMA 1 Montong Gading for the 2020/2021 academic year. The type of research used is experimental. Data collection techniques are interviews and documentation. The data analysis techniques in this research are descriptive analysis techniques and independent data analysis techniques. The results of the analysis conducted in class XI of SMAN 1 Montong Gading by looking at the students' speaking ability using the Role Play Method and has been tested statistically to obtain a t-count result that is greater than t-table. the results of the t-test obtained t-count = 5.23 at a significant level = 5% with degrees of freedom = n1+ n2-2 = 34+34-2 = 66, so that the experimental class showed an increase. These results were obtained by using hypothesis testing with t-test, from the calculation it can be calculated = 5.23 while t table = 2.00 which means t count > ttable which states HO is rejected and Ha is accepted. This shows that there is a significant impact between the experimental class and the control class on students' speaking ability by role play method. Keywords : Role Play, Communication Skill, Experiment